PRA- RANCANGAN INDUSTRI OLAHAN VANILI (VANILLA PLANIFOLIA ANDREWS) DENGAN SISTEM PENGERINGAN LAMPU PIJAR: PENGERINGAN VANILI (VANILLA PLANIFOLIA ANDREWS) PADA SISTEM PENGERINGAN SEDERHANA DENGAN PERLAKUAN LAMPU PIJAR DAN SIRKULASI UDARA - Kamahsari, Isti
Vanilla (Vanilla planifolia Andrews) is a tropical plantation plant that has many uses and high economic value. Indonesia ranks second in the world's largest vanilla exporter and producer. In 2017, Indonesia can produce about 2,402 tons of vanilla. Dried vanilla has a much higher selling value and better quality than fresh vanilla. The drying process is a step that really determines the quality of dried vanilla. The average farmer is still drying in the traditional way which still depends on weather conditions, so it requires a long drying time and the quality is difficult to standardize. Research on drying vanilla using a simple dryer with incandescent light and air circulation has been carried out in Jatinangor for 2 months in order to determine the optimal drying conditions and tools. Vanilla for 9 months was dried in a dryer for 24 hours, which was repeated 3 times. Experiments were carried out with a one-variable-at-a-time (OVAT) experimental design, with the variables being tested, namely fan voltage (4V, 6V, and 8V) and drying load capacity (1 tray, 2 trays, and 3 trays). The results showed that vanilla, dried with a fan voltage of 6V and a load capacity of 3 trays had an SEC value of 3.682 kWh/kg, an energy efficiency value of 0.94%, an effective diffusivity value of 6.7616 x 10-12 m2/s and an energy value. Activation of 25.75 Watt/kg. The vanillin content and ash content after drying were 4.225% and 2.14%. The mathematical model which is suitable for drying vanilla is obtained by Wang & Singh's model. So that the most optimal drying tools is a dryer with a fan voltage of 6V and a drying load capacity of 3 trays.